Raincoat Bag / Nor Amira Ishak - Ishak, Nor Amira (2020)
All people will face raining season that occur every year and that is why many people need equipment to protect themselves from rain, such as poncho, raincoat and umbrella. When it comes to rain, they can also be sensitive to cold weather, especially for people who have to go through raining for a long journey. This is why many peoples have to face a various problem during raining as the weather changes on a daily basis cannot be predicted by anyone unless they watch the climate conditions predicted by meteorologists every morning in news or weather reports before they start their daily routine. In addition, there are still some people who sometimes forget to make an early preparation, such as always carrying an umbrella or poncho in their bag packs or handbags.